2007
DOI: 10.1007/s11270-007-9528-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Diffuse Phosphorus Pollution during Rewetting of Fen Peat Soils: A Trans-European Case Study

Abstract: Intensive cultivation of fen peat soils (Eutric Histosols) for agricultural purposes, started in Europe about 250 years ago, resulting in decreased soil fertility, increased oxidation of peat and corresponding CO 2 -emissions to the atmosphere, nutrient transfer to aquatic ecosystems and losses in the total area of the former native wetlands. To prevent these negative environmental effects set-aside programs and rewetting measures were promoted in recent years. Literature results and practical experiences show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…Litaor et al, 2004;Richardson, 1985;Sah and Mikkelsen, 1986;Schlicting et al, 2002). During anoxic conditions redox sensitive Fe(III) oxides are subjected to microbial induced reductive dissolution, which may lead to changes in sorption properties (Heiberg et al, 2010), and concurrent release of Fe(II) and dissolved P. Numerous investigations have reported increased Fe and P concentrations in soil pore water following reduction in soil redox potential Meissner et al, 2008;Moore and Reddy, 1994;Pant et al, 2002;Rupp et al, 2004;Sallade and Sims, 1997;Scalenghe et al, 2002;Young and Ross, 2001). It is thus, widely recognized that restored wetlands could potentially become a source of P that may cause eutrophication in downstream recipients (Aldous et al, 2005;Hoffmann et al, 2009;Pant and Reddy, 2003;Phillips, 2001;Zak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Litaor et al, 2004;Richardson, 1985;Sah and Mikkelsen, 1986;Schlicting et al, 2002). During anoxic conditions redox sensitive Fe(III) oxides are subjected to microbial induced reductive dissolution, which may lead to changes in sorption properties (Heiberg et al, 2010), and concurrent release of Fe(II) and dissolved P. Numerous investigations have reported increased Fe and P concentrations in soil pore water following reduction in soil redox potential Meissner et al, 2008;Moore and Reddy, 1994;Pant et al, 2002;Rupp et al, 2004;Sallade and Sims, 1997;Scalenghe et al, 2002;Young and Ross, 2001). It is thus, widely recognized that restored wetlands could potentially become a source of P that may cause eutrophication in downstream recipients (Aldous et al, 2005;Hoffmann et al, 2009;Pant and Reddy, 2003;Phillips, 2001;Zak et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations carried out shortly after the initiation of rewetting processes often exhibited a significant release of NH 4 eN, SRP and DOC (Kiekbusch and Schrautzer, 2007;Zak and Gelbrecht, 2007;Meissner et al, 2008;Finnegan et al, 2014). The authors concluded that these processes enhance eutrophication in water bodies, impairing the surrounding ecosystems.…”
Section: Prevailing Processesmentioning
confidence: 99%
“…Os valores de Eh e de pH para E1 (Quadro 2) apresentam-se semelhantes aos encontrados na literatura sobre efeito de ambiente redutivo proporcionado por inundação (Scalenghe et al, 2002;Meissner et al, 2008). Ao aumentar o tempo de contato para 60 dias (E4), com trocas de soluções aos 30 dias (E2) e aos 45 dias (E3), os valores de Eh, de modo geral, voltam a aumentar.…”
Section: Alterações No Potencial Redox E Hidrogeniônicounclassified